Strategi Kepala Madrasah dalam Pembentukan Disiplin Belajar Siswa Melalui Program Tahfidz Qur’an di MTs Ma’arif Curug Cijulang - Ulpah Nupusiah (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
Management strategy is a plan that can determine a manager's planning in a directed manner towards long-term goals accompanied by the preparation of efforts on how to achieve the expected goals. The problem in the background of this study is related to the principal's strategy in forming the character of student learning discipline through the Quran memorization program because of the decline in the spirit of learning from students. This study focuses on the management strategy used by the principal in forming the character of student learning discipline through the Quran memorization program. This study uses a qualitative method, with the research subjects being the principal, the Quran memorization teacher and students. The study was conducted at MTs Ma'arif Curug Cijulang. The data collection techniques used in this study were observation, interviews, and documentation. The data analysis techniques used were data reduction, data presentation, and drawing conclusions. The results of the research can be concluded that the strategies implemented by the madrasah head show an increase in student learning discipline, both is terms of time, compliance with rules, and daily attitudes. This proves the success of the Tahfidz Al-Qur’an program in forming students’ disciplined learning character which is implemented through the stages of strategy formulation, strategy implementation and strategy evaluation.